A software platform for phase contrast x-ray breast imaging research. (1st June 2015) - Bliznakova, K.; Russo, P.; Mettivier, G.; Requardt, H.; Popov, P.; Bravin, A.; Buliev, I.
Abstract: Purpose: To present and validate a computer-based simulation platform dedicated for phase contrast x-ray breast imaging research. Methods: The software platform, developed at the Technical University of Varna on the basis of a previously validated x-ray imaging software simulator, comprises modules for object creation and for x-ray image formation. These modules were updated to take into account the refractive index for phase contrast imaging as well as implementation of the Fresnel–Kirchhoff diffraction theory of the propagating x-ray waves. Projection images are generated in an in-line acquisition geometry. To test and validate the platform, several phantoms differing in their complexity were constructed and imaged at 25 keV and 60 keV at the beamline ID17 of the European Synchrotron Radiation Facility. The software platform was used to design computational phantoms that mimic those used in the experimental study and to generate x-ray images in absorption and phase contrast modes. Results: The visual and quantitative results of the validation process showed an overall good correlation between simulated and experimental images and show the potential of this platform for research in phase contrast x-ray imaging of the breast. The application of the platform is demonstrated in a feasibility study for phase contrast images of complex inhomogeneous and anthropomorphic breast phantoms, compared to x-ray images generated in absorption mode. Conclusions: The improved visibility of mammographic structures suggests further investigation and optimisation of phase contrast x-ray breast imaging, especially when abnormalities are present. The software platform can be exploited also for educational purposes. Highlights: A simulation platform dedicated for PhC x-ray breast imaging research is developed. Various in complexity phantoms for PhC (from simple cuboids to anthropomorphic breasts) are modelled. Generation of PhC images from thick objects (breast models) is now feasible. Simulation results are validated against measurements performed at ESRF. Experimental studies on PhC may be optimized in advance.